Evaluation and control of microbial and chemical contamination in dialysis water plants of Italian nephrology wards. Issue 2 (October 2017) - Totaro, M.; Casini, B.; Valentini, P.; Miccoli, M.; Giorgi, S.; Porretta, A.; Privitera, G.; Lopalco, P.L.; Baggiani, A.
Summary: Background: Patients receiving haemodialysis are exposed to a large volume of dialysis fluid. The Italian Society of Nephrology (ISN) has published guidelines and microbial quality standards on dialysis water (DW) and solutions to ensure patient safety. Aim: To identify microbial and chemical hazards, and evaluate the quality of disinfection treatment in DW plants. Methods: In 2015 and 2016, water networks and DW plants (closed loop and online monitors) of nine dialysis wards of Italian hospitals, hosting 162 dialysis beds overall, were sampled on a monthly basis to determine the parameters provided by ISN guidelines. Chlorinated drinking water was desalinated by reverse osmosis and distributed to the closed loop which feeds all online monitors. Disinfection with peracetic acid was performed in all DW plants on a monthly basis. Findings: Over the 24-month study period, seven out of nine DW plants (78%) recorded negative results for all investigated parameters. Closed loop contamination with Burkholderia cepacia was detected in a DW plant from January 2015 to March 2015. Pseudomonas aeruginosa was isolated from March 2016 to May 2016 in the closed loop of another DW plant. These microbial contaminations were eradicated by shock disinfection with sodium hypochlorite and peracetic acid, followed by water flushing. Conclusion: These results highlight the importance of chemical and physical methods of DW disinfection. The maintenance of control measures in water plants hosted in dialysis wards ensures a microbial risk reduction for all dialysis patients.